Developing A Video Copywriting to Promote Palembang Traditional Cakes - M. Nadjmuddin; Nabilla, Rizka; Kurniati, Depi; Lutfiyatun, Eka; Algis Akbar; Rahma Fadhillah (Samarinda State Polytechnic, 2023)
In terms of trading, a place of business needs to be known by many people in order to become buyers, because buyers have an important role that affects increasing sales and business growth. Unfortunately, there are still local people and tourists who do not know the location of the business and the uniqueness of the products they sell. To ensure that Dapoer Bunda Rayya becomes known to both local people and tourists, it is necessary to promote the business. Based on the statement above, the researchers introduced and promoted Dapoer Bunda Rayya as the seller and maker of Palembang traditional cakes through advertising videos. The study aims to know video copywriting process of Dapoer Bunda Rayya in two languages, English and Bahasa Indonesia, for promoting Palembang traditional dessert. This research was conducted using the Research & Development approach with the preliminary study, model draft, and final product testing and dissemination stages. Data was collected through interviews, observations, and questionnaires. The researchers wrote the copy by using PAS formula, the AIDA formula, and the steps of writing a copy by Rieck. After the final copywriting was approved it was posted on social media. The video copywriting was an effective media to introduce the new innovation cakes and also another typically Palembang cakes for local and international tourists.